2011
DOI: 10.1007/s12640-011-9278-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, Neurochemical and Histological Alterations Promoted by Bilateral Intranigral Rotenone Administration: A New Approach for an Old Neurotoxin

Abstract: Rotenone exposure in rodents provides an interesting model for studying mechanisms of toxin-induced dopaminergic neuronal injury. However, several aspects remain unclear regarding the effects and the accuracy of rotenone as an animal model of Parkinson's disease (PD). In order to counteract these limitations, this study characterized a precise neurotoxin-delivery strategy employing the bilateral intranigral administration protocol of rotenone as a reliable model of PD. We performed bilateral intranigral inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
6
24
0
Order By: Relevance
“…In this model, a massive inhibition of mitochondrial complex I produces selective degeneration of the dopaminergic nigrostriatal system and reproduces key pathological features of clinical PD (Sherer et al, ; Alam and Schmidt, ). The present study showed that intranigral rotenone did not altered the motor parameters at the time points analyzed, corroborating our recent findings (Moreira et al, ). However, REMSD elicited an increase of ambulatory distance per se and also generated an increment in this parameter of the rotenone REMSD compared with the sham control group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this model, a massive inhibition of mitochondrial complex I produces selective degeneration of the dopaminergic nigrostriatal system and reproduces key pathological features of clinical PD (Sherer et al, ; Alam and Schmidt, ). The present study showed that intranigral rotenone did not altered the motor parameters at the time points analyzed, corroborating our recent findings (Moreira et al, ). However, REMSD elicited an increase of ambulatory distance per se and also generated an increment in this parameter of the rotenone REMSD compared with the sham control group.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, this neurotransmitter was intensely modulated by REMSD and rotenone. That is, striatal DA levels were reduced after rotenone, supporting recent findings (Santiago et al, ; Moreira et al, ). In addition, REMSD also caused an increment in DOPAC, HVA, and in DA turnover, which could be interpreted as an attempt to compensate for this increased neurotransmitter degradation, which is a classical mechanism of plasticity, also observed with neurotoxins (Hsieh et al, ; Ariza et al, ; Barbiero et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We noted the impairment of motor coordination in rotenone-treated-group for 3 months, as well as alpha-synuclein inclusions in the dopaminergic neurons of the SN pc . These results suggested chronic intragastrical administrated rotenone replicated successfully the classical features of PD in the present study, which conformed to other reports [26], [27]. Rotenone can induce gastrointestinal tract dysfunction as determined by alpha-synuclein aggregation in the enteric nervous system (ENS), loss of myenteric neurons of the small intestine [28], a delay in gastric emptying, and impaired functioning of inhibitory neurons in the ENS [29].…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, the present study revealed that DA content as well as the metabolites; DOPAC and HVA levels were reduced in the striatum of ROT‐treated rats with increase in the DA turnover supporting by the studies of Moreira et al () and Tong et al ().…”
Section: Discussionsupporting
confidence: 91%